Inhibiting the inflammasome: one domain at a time - Dorfleutner, Andrea (Immunol Rev, 2015)
Inflammasomes are protein complexes that promote the maturation and release of pro-inflammatory cytokines and danger signals as well as pyroptosis in response to infections and cellular stress. Inflammasomes consist of a sensor, an adapter, and the effector caspase-1, which interact through homotypic interactions of caspase recruitment domains (CARDs) or PYRIN domains (PYDs). Hence, decoy proteins encoding only a CARD or PYD, COPs and POPs, respectively, are assumed to inhibit inflammasome assembly. Sensors encoding a PYD belong to the families of NOD-like receptors containing a PYD (NLRPs) or AIM2-like receptors (ALRs), which interact with the PYD and CARD-containing adapter ASC through homotypic PYD interactions. Subsequently, ASC undergoes PYD-dependent oligomerization, which promotes CARD-mediated interactions between ASC and caspase-1, resulting in caspase-1 activation. POPs are suggested to interfere with the interaction between NLRPs/ALRs and ASC to prevent nucleation of ASC and therefore prevent an oligomeric platform for caspase-1 activation. Similarly, COPs are suggested to bind to the CARD of caspase-1 to prevent its recruitment to the oligomeric ASC platform and its activation. Alternatively, the adapter ASC may regulate inflammasome activity by expressing different isoforms, which are either capable or incapable of assembling an oligomeric ASC platform. The molecular mechanism of inflammasome assembly has only recently been elucidated, but the effects of most COPs and POPs on inflammasome assembly have not been investigated. Here we discuss our model of COP and POP-mediated inflammasome regulation.